STUDENTS’ PERCEPTION ON ENGLISH TEACHING USING A VIRTUAL SYSTEM ONLINE LEARNING - Rahma, Andi Sri Fatul; Qalbi, Nur; Andi Baso, Farisha (FKIP Unismuh Makassar, 2021)
The objectives of this research were to find out the students’ perception of the use of Google meet application in English learning at eleventh grade students of MA Guppi Samata Gowa. The researcher used quantitative descriptive research. The sample of this research was eleventh grade students of MA Guppi Samata Gowa which consist of 20 students. The sample was taken by using questioner with Google form. Based on the findings, it was found that students gave positive perception on the use of Google meet in teaching English, the positive response came from their experience in learning process. The result of the research indicated that based on the Likert’s score analysis there were 12 (85,7%) out of the students was categorized positive perception in which score classification is 42-70, beside that there were 2 students (14,3%) had neutral perception and none of students have negative perception. It was categorized that Google meet used in teaching English effective to apply, it helps the learning teaching process in the class. The recommendation for the future research to conduct a research related to the using of Google meet in teaching and learning procces such as kahoot, as the advance of tecnology keep increasing time by time.